Improvement of engineered thermostable xylanase production via immobilization of recombinant escherichia coli onto graphene oxide - Nor Ashikin, Nur Atiqah Lyana (2020)
Escherichia coli is the preference host system for enzyme production by recombinant DNA technology. This was due to its promising trait that is suitable for genetically modify and the obtainability of a difference E. coli strains. But, the main downside when utilizing E. coli as a host is bacterial cell lysis due to the pressure build-up through overproduction of the expressed recombinant enzyme in the periplasmic space. Thus, the utilization of the immobilization in targeting the recombinant enzyme expression in the culture medium, presents substantial preferences over cytoplasmic excretion. Immobilization process can be applied to optimize the operational performance system of cell for industrial applications which leads to the development of economically and ecologically available enzyme such as xylanase. In this study, the effects of graphene oxide (GO) on xylanase excretion and ~-galactosidase activity of immobilized E. coli was examined. The experiments were performed under the optimized RSM conditions (20°C, 0.5 mM, IPTG and pH 7) using shake flask cultivation followed by bioreactor conditions (20°C, 0.5 mM, IPTG and pH 7) in batch fermentation. The immobilized cells onto GO using shake flask cultivation exhibit about 3.8-fold increase in xylanase production (0.4821 U/ml) or equal to 73.7% higher compared to free cells (0.1264 U/ml). The E. coli were also demonstrated 15.3% reduction of cell lysis (0.0299 Vlml of ~-galactosidase activity) compared to free cells (0.1273 U/ml of ~-galactosidase activity) and 72.6% increase in plasmid stability compared to free cells. The xylanase concentration was 0.482 Vlml, representing 99.4% of the predicted value (0.485 U/ml) and l.71-fold higher than the value before optimization process (0.283 U/ml). The occurrence of cell lysis demonstrated 99.3% reduction and increased in the plasmid stability up to 87% under the optimized RSM condition compared to free cells. The stirrer tank bioreactor also showed 5% higher in xylanase excretion (0.506 Vlml) with 33% reduction of ~-galactosidase activity (0.06 U/ml) compared to shake flask cultivation (0.09 U/ml) after 24h. While from the Liquid Chromatography Mass Spectometry (LCMS) analysis showed that the xylooligosaccharides was found to be hydrolyzed by an endoxylanase to produce xylopentaose sugar. Hence, this study demonstrated that the immobilization of E. coli on GO potentially to be valuable for the excretion of recombinant proteins in E. coli with high cell viability.